A study of iron status in children with cyanotic congenital heart disease - Bandyopadhyay, Sudipta; A., Bhuvaneswari; Sridhar, Anuradha (International Journal of Contemporary Pediatrics, 2023)
Background: Iron deficiency is a common problem in patients with cyanotic congenital heart disease (CCHD), but it is often underdiagnosed. Cyanotic patients with iron deficiency will experience higher morbidity due to symptoms of hyper viscosity. The consequences of iron deficiency anemia in cyanotic heart disease may manifest either in infancy or later. The tendency to develop metabolic acidosis and hyper-cyanotic attacks is exacerbated by relative iron deficiency anemia. This study was performed to identify the prevalence of iron deficiency in children with CCHD based on definitive tests like serum ferritin. Methods: We included 100 patients with congenital cyanotic heart diseases between 3 months to 18 years. Baseline characteristics were noted in specific proforma. Data from the blood tests were collected and analysed statistically to find out the prevalence of iron deficiency, along with tests that best predict the presence of iron deficiency. Results: Serum ferritin-based prevalence of iron deficiency in CCHD was 46%. Iron status based on haemoglobin, MCV values with the serum ferritin, and the strength of agreement were almost perfect. The strength of agreement for PCV, MCH, RDW, and peripheral smear was substantially significant. The strength of agreement for MCHC was moderate significance (Kappa value 0.41-0.60). Red cell distribution width (RDW) was an independent predictor of iron deficiency in logistic regression analysis. Conclusions: RDW seems to be a good indicator for predicting iron deficiency in children with congenital cyanotic heart diseases.